If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -4x + -32 Reorder the terms: 0 = -32 + -4x Solving 0 = -32 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 0 + 4x = -32 + -4x + 4x Remove the zero: 4x = -32 + -4x + 4x Combine like terms: -4x + 4x = 0 4x = -32 + 0 4x = -32 Divide each side by '4'. x = -8 Simplifying x = -8
| 0=28x^2-12x | | 10m+7n=170 | | 7x^2-16x=18 | | x^2-x=25 | | 14x^2*2x+3=0 | | (ax+c)(bx+d)=(bx+c)(ax+d) | | 10d-8=3d-17-2d | | 7x+16-3x=12-6x-6 | | 6x+y=8 | | S=3(r^3)t | | p-5=-12+p | | S=3r^3t | | 2a-5+12c=2a+b | | 5z-12=5z+15 | | (13x-25)+(9x+3)=77 | | -100x=10x^2 | | (0.1x+1)*.1x=2x | | -5(t-1)+9t=7t-6 | | 83=x+59 | | 63-n=15 | | 7+5b=37 | | 42-5=x | | 6+3+c=19 | | (5x-6)+(2x+5)=180 | | 17-x=16-5 | | 37-12=c-5 | | 6+2+n=19 | | 56=x-7 | | -.3y+.1=.5 | | 50-t^2=0 | | 3x+6y=39 | | 9z-z=-1+6z-3-2 |